Initial Study of Thoicyianate Microbial Degradation by Isolates from Poluted Soil in Gold Mining Area in Indonesia - Maman Rahmansyah; Dwi Agustiyani Muslichah (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2018)
This study was conducted to clarify the ability of denitrifying bacterial group utilized nitrogen (N) due to decompose N in thiocyanate structure.Thiocyanate is a chemical that has likely pollutant to the environment, produced by some industrial activities. Denitrifying bacterial group obtained from bulk of sluge samples collected from the gold tailing, and some soil samples collected suround the gold mining site. The samples then were taken to the Microbiology Laboratory, Research Center for Biology, to investigate. Samples were initially acclimatized by potassium nitrate (KNO3), acetonitrile, and liquid waste or sludge. The result showed that denitrifying bacteria in the samples utilize 60 to 90% NO3-N (nitrate) in 42 days incubation. Isolation process were then conducted in each samples, and four denitrification bacterial, named as AN, Ea, L7T5, and PETI-7 isolates were attained. The isolates formerly cultured in a denitrifying bacterial medium containing KSCN (Potassium Thiocyanate), amended with glucose and sodium acetate for carbon source. Those four isolates performed satisfactory in aerobic and anaerobic cultures medium to denitrifying process, and utilize glucose and sodium acetate as co-carbon source, but all bacterial isolates were unable to use thiocyanate as the single carbon source. Thiocyanate degradation performed by the isolates through a simultaneous conversion along with denitrification process. This phenomenon turn to open the opportunity on role of application denitrifying bacteria become bioresources material in efforts to decompost thiocyanate.